Tingkat Keamanan dan Kemudahan Transaksi pada Toko Offline Terhadap Keputusan Pembelian Action Figure Original - Mahatmana Krisna Herduna Putra; Destina Paningrum; Rusnandari Retno Cahyani (Universitas Sahid Surakarta, 2022)
Security and ease of transactions is one of the factors that play a role in influencing purchasing decisions. The development of an increasingly modern eraencourages the creation of a new transaction system that can be used easily, but with a level of security that is not fully guaranteed.The method used in this research is descriptive quantitative by collecting data using a digital questionnaire, namely Google Form, to collectors of Original Action Figures in the Residency of Surakarta. The variables used in this study are the level of security (X1) and the level of convenience (X2) as independent variables and purchasing decisions (Y) as the dependent variable. The results of this study prove that the level of security and ease of transactions at offline stores partially and simultaneously influences purchasing decisions.